Penerapan Video Tutorial Membuat Tusuk Dasar Menjahit untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Teknologi Menjahit Kelas X SMK Negeri 3 Kediri - Kharirotur Rikza Putri Ardiyono; Urip Wahyuningsih; Marniati Marniati; Irma Russanti (Journal on Education, 2024)
The purpose of this research is to determine the activities, responses and influence of students grades on the application of video tutorial-based learning media for making basic sewing stitches for class X Fashion Design 2 students at SMKN 3 Kediri. The type of approach used is a quantitative approach and a pre-experimental research design with one group pre-test and post-test. The subjects in this research were 32 students of Class X Fashion Design 2 at SMKN 3 Kediri. The method for collecting data is by using observation, tests, or questionnaires. The data analysis technique used is quantitative descriptive techniques. In the teacher observation data, all aspects received an average of 3.66 with very good criteria. Meanwhile, student observations got an average of 3.28 in the very good category. Student responses received an average of 93.8% in the very good category. Student learning outcomes using video tutorials achieved completeness with a classical percentage of 100%, namely with an average pre-test of 71.4 and post-test of 91.56. The findings of this research can help students understand the material so that they achieve completeness with a score that exceeds the minimum completeness criteria (KKM).